PENGARUH RASIO KEUANGAN CAMEL TERHADAP KONDISI DI BANK PERKREDITAN RAKYAT KABUPATEN TABANAN - Nuryadiputra, Nyoman Ariyoga (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The research aims to analyze the probability of troubled rural bank credit conditions that are influenced by CAMEL ratio with the proxies are the ratio of CAR, NPL, PPAP, NPM , ROA, BOPO, and LD R . P opulation in the study is the Conventional Rural Credit Bank located in Tabanan Regency. The sample is determined by the saturated sample method, so the number of samples is 19 banks for 3 years observation from 2015 to 2017, so that 57 observations are obtained. Data analysis was carried out by logistic regression techniques with a significance level of 5%. The results showed that the CAR, NPM, and ROA ratios had a negative effect on the probability of troubled conditions for rural banks in Tabanan Regency. Other variables such as NPL, PPAP, BOPO, and LDR have a positive effect on the probability of problematic conditions at BPR in Tabanan Regency.